1993
DOI: 10.1016/0014-2999(93)90522-j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic administration of adenosine A1 receptor agonist and antagonist on spatial learning and memory

Abstract: Spatial memory acquisition in Morris water maze was tested in C57BL/6 mice. Animals were injected once daily with different doses of either N 6 -cyclopentyladenosine (CPA) or 8-cyclopentyl-1,3-dipropylxanthine (CPX). Drugs were administered for 9 days either concurrently with water maze testing (drugs injected 1 h after each trial), or prior to the entire block of trials. In the latter case, 1 day without injections preceded water maze experiments. Chronic administration of CPA resulted in a significant, dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 32 publications
3
38
1
Order By: Relevance
“…The absence of deficits observed in the Morris water maze thus indicates that such life-long administration does not cause any major effects on memory. This is in apparent contrast to a study where chronic administration of the selective A 1 R antagonist CPX was shown to impair performance in the water maze (Von Lubitz et al, 1993), even though no effect was observed after acute administration. In a recent report (2003), Lang et al also confirmed that the deletion of A 1 R does not affect spatial performance during both training and probe trials in a place navigation task in the water maze, although their A 1 R −/− mice showed increased wall hugging, a strategy choice suggested to be a result of their emotional instability.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The absence of deficits observed in the Morris water maze thus indicates that such life-long administration does not cause any major effects on memory. This is in apparent contrast to a study where chronic administration of the selective A 1 R antagonist CPX was shown to impair performance in the water maze (Von Lubitz et al, 1993), even though no effect was observed after acute administration. In a recent report (2003), Lang et al also confirmed that the deletion of A 1 R does not affect spatial performance during both training and probe trials in a place navigation task in the water maze, although their A 1 R −/− mice showed increased wall hugging, a strategy choice suggested to be a result of their emotional instability.…”
Section: Discussioncontrasting
confidence: 99%
“…The hippocampal formation is enriched with A 1 Rs (Fastbom et al, 1987;Svenningsson et al, 1997) and these receptors may be involved in the development and consolidation of longterm potentiation (LTP) (Arai et al, 1990;de Mendonca and Ribeiro, 1990;Alzheimer et al, 1991;Forghani and Krnjevic, 1995) and in induction of long-term depression (LTD) (de Mendonca et al, 1997;Bon and Garthwaite, 2002;Moore et al, 2003). Selective A 1 R agonists and antagonists have been reported, respectively, to impair and to facilitate learning and memory in passive-avoidance tasks (e.g., Normile et al, 1991;Suzuki et al, 1993;Pereira et al, 2002) and spatial learning in mazes (e.g., Suzuki et al, 1993;Von Lubitz et al, 1993), and have been proposed as therapy in cognitive disorders (reviewed by Erfurth and Schmauss, 1995). However, if given at high doses, antagonists produce an impairment (Zarrindast and Shafaghi, 1994), perhaps reflecting a biphasic action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenosine A 1 -receptor up and down regulation by chronic treatment with adenosine A 1 -receptor antagonists and agonists, respectively, has been reported to modulate cerebral ischemia, seizures, spatial learning, and memory (Von Lubitz et al 1993a,b, 1994a, but little is known about the physiological consequences of adenosine A 1 -receptor upregulation for their coupling to signal transduction systems. In general, there are only few reports in the literature that examine the consequences of changes in receptor expression for their signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have shown previously that G-protein and PLC contents of all cultures are comparable (measured by a direct activation of Gi/o-proteins by mastoparan) (Biber et al 1997). Moreover, there are no data available at the moment indicating that CBZ might have any effect on G-protein and/or PLC activity or expression or inositol phospholipid metabolism.Adenosine A 1 -receptor up and down regulation by chronic treatment with adenosine A 1 -receptor antagonists and agonists, respectively, has been reported to modulate cerebral ischemia, seizures, spatial learning, and memory (Von Lubitz et al 1993a,b, 1994a, but little is known about the physiological consequences of adenosine A 1 -receptor upregulation for their coupling to signal transduction systems. In general, there are only few reports in the literature that examine the consequences of changes in receptor expression for their signal transduction.…”
mentioning
confidence: 99%